An Efficient Approach to the Synthesis of Novel Oxazolidinones as Potential Antimicrobial Agents - Kavita Devi; Yumna Asmat; Sonika Jain; Swapnil Sharma; Jaya Dwivedi (Journal of Chemistry)
Oxazolidinone, either mononuclear or condensed with other heterocyclics, has established its importance in medicinal chemistry. A variety of biological activities have been reported by oxazolidinone derivatives. The present work describes the synthesis of several oxazolidinone derivatives, 3-(2-(7-chloroquinoline-4-ylamino)ethyl)-2-imino-5-(4-chloro/nitro/methoxy benzylidene)oxazolidin-4-one 4(a–c) and 4-(2-(7-chloroquinolin-4-ylamino)ethyl)-2(4-chloro/nitro/methoxy-benzylidene)-1,6-diox-4,9-di-azaspiro[4,4]nonane-3,8-dione 5(a–c). Synthesized compounds (1, 3, 4a, 5a, and 5c) were screened against bacterial strains such as S. aureus (MTCC 96) and E. coli (MTCC119) and fungal strains A. niger (MTCC 1344) and C. albicans (MTCC 871) compared with penicillin for bacteria and fluconazole for fungi as reference drugs by disk diffusion method. All synthesized compounds were identified by the means of IR, NMR, and MS.